Nimesulide in the treatment of osteoarthritis - Mauro Bianchi; Marco Broggini (Publiediting, 2005)
Osteoarthritis (OA) is the most common joint disorder among the world's population. It is costly and a major cause of pain and disability, especially in the elderly. The main aims of pharmacotherapy for OA are to provide pain relief, reduce inflammation, maintain movement and to positively affect the natural course of this disease by reducing the degradation of joint cartilage. The severity of pain often prompts treatment with nonsteroidal anti-inflammatory drugs (NSAIDs), which are commonly used. Many patients with symptomatic OA cannot manage without them. World-wide experience with nimesulide confirms that it is a NSAID with good analgesic efficacy and a number of pharmacological properties that may result particularly favourable in the treatment of joint diseases. In the last few years several controlled studies have been done in order to investigate its effects in patients with OA. The objective of this review is to deal with some aspects concerning the main features of OA and to point out the role of nimesulide as a drug particularly effective in the treatment of this disease.